Corporate governance disclosure and share price accuracy: Empirical evidence from the United Arab Emirates. Issue 2 (14th September 2015) - ElKelish, Walaa Wahid; Hassan, Mostafa Kamal
Abstract : Purpose: – The purpose of this paper is to investigate the impact of corporate governance disclosure on share price accuracy of listed companies in the United Arab Emirates (UAE). Design/methodology/approach: – Data on corporate governance disclosure were obtained from the financial statements of companies listed in the UAE stock market, and share price accuracy indices were crafted from each company's weekly share price returns between 2008 and 2009, using generalized least squares regression analysis. Multiple regression analysis with fixed effects was then implemented to test the study hypotheses. Findings: – Voluntary corporate governance disclosure has a significant positive impact on share price accuracy. There is also evidence that mandatory corporate governance disclosure plays an important positive role on share price accuracy in the UAE business environment. Research limitations/implications: – This paper covers a two-year transitional period during implementation of a new corporate governance code in the emerging market of the UAE. Practical implications: – This paper encourages corporate managers in the UAE, as well as in other countries with similar business conditions, to review their voluntary corporate governance disclosure policies in accordance with international good practice. The authors suggest that regulators and accounting standard setters should extend mandatory corporate governance disclosure rules for the benefit of stock market participants and the overall welfare of the economy. Originality/value: – This paper extends the literature on the relationship between accounting disclosure and share price accuracy to include corporate governance disclosure in emerging market economies such as the UAE. It also shows the importance of both voluntary and mandatory corporate governance disclosure.